2017
DOI: 10.3390/medicines4010009
|View full text |Cite
|
Sign up to set email alerts
|

Vochysia rufa Stem Bark Extract Protects Endothelial Cells against High Glucose Damage

Abstract: Background: Increased oxidative stress by persistent hyperglycemia is a widely accepted factor in vascular damage responsible for type 2 diabetes complications. The plant Vochysia rufa (Vr) has been used in folk medicine in Brazil for the treatment of diabetes. Thus; the protective effect of a Vr stem bark extract against a challenge by a high glucose concentration on EA.hy926 (EA) endothelial cells is evaluated. Methods: Vegetal material is extracted with distilled water by maceration and evaporated until dry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 25 publications
6
10
0
Order By: Relevance
“…The dose-dependent recovery of GSH concentration when SH-SY5Y cells were pre- or co-treated with both aqueous and ethanolic S. nigra extracts unequivocally indicates an efficient cellular chemo-protection against the oxidative insult. As in the case of ROS levels, similar results have been reported with other plant extracts rich in antioxidant compounds such as flavonoids and hydroxycinnamic acids in different cell types; for instance, Corema album [ 29 ], green coffee [ 30 ], cranberry [ 31 ], Vochysia rufa [ 37 ], Silybum marianum [ 38 ], and cocoa [ 39 ]. However, this is the first time that a protective effect on GSH has been shown by a plant extract in stressed neuroblastoma cells.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The dose-dependent recovery of GSH concentration when SH-SY5Y cells were pre- or co-treated with both aqueous and ethanolic S. nigra extracts unequivocally indicates an efficient cellular chemo-protection against the oxidative insult. As in the case of ROS levels, similar results have been reported with other plant extracts rich in antioxidant compounds such as flavonoids and hydroxycinnamic acids in different cell types; for instance, Corema album [ 29 ], green coffee [ 30 ], cranberry [ 31 ], Vochysia rufa [ 37 ], Silybum marianum [ 38 ], and cocoa [ 39 ]. However, this is the first time that a protective effect on GSH has been shown by a plant extract in stressed neuroblastoma cells.…”
Section: Discussionsupporting
confidence: 75%
“…In previous works, we have shown a chemo-protective effect with 0.5–50 µg/mL of cocoa phenolic extract [ 25 , 28 , 36 ], 1–40 µg/mL of Corema album extract [ 29 ], 1–50 µg/mL of green coffee bean extract [ 30 ] and 0.5–50 µg/mL of cranberry extract [ 31 ] on cultured hepatic cells. Similarly, we have reported chemo-protective activity for 0.5–100 µg/mL Vochysia rufa extract [ 37 ], 5–25 µg/mL Silybum marianum [ 38 ], and 2.5–20 µg/mL cocoa extract [ 39 ] in cultured endothelial cells. Since these ranges of concentrations, not far from realistic, showed a chemo-protective effect against oxidative stress in different cell lines, a similar range of concentrations was assayed in cultured neuroblastoma cells and their response in oxidative stress conditions as well as their effect on the autophagy process was tested.…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, levels of 30–40 µM of cranberry phytochemicals have been detected in plasma after the intake of cranberry juice [ 35 , 36 ]. Hence, the range of D. tortuosum extract concentrations tested is not far from realistic; in fact, in previous works we have report the protective activity of Vochysia rufa (0.5–100 µg/mL) [ 21 ], Silybum marianum (5–25 µg/mL) [ 20 ], and cocoa extract (2.5–20 µg/mL) [ 23 ] in EA.hy926 cells. Additionally, we have recently reported that doses of 5–25 µg/mL of a Sambucus nigra extract [ 28 ] and 25–200 µg/mL of an aqueous extract of cocoa phenolic compounds [ 27 ] protect SH-SY5Y cells from oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, by using EA.hy926 cells, we have shown the protective effect of an extract from Silybum marianum , rich in flavonol derivatives known as flavonolignans, on cultured endothelial cells subjected to high glucose concentrations [ 20 ]. In the same model, Vochysia rufa stem bark extract, rich in reducing sugars and flavonoids, also showed significant protection against high glucose damage [ 21 ]. Similarly, in yerba mate and green coffee extracts, their main hydroxycinnamic acids and microbial metabolites prevented Tumor Necrosis Factor-alpha (TNF-α)-induced inflammation [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…An in vitro model of diabetes was studied to evaluate the potential of the PRF on protecting HUVECs as an endothelial cell model from high glucose-induced cytotoxicity before proceeding further with an in vivo study. Previous studies have reported that high concentrations of glucose can cause endothelial cell damage, leading to increased cell apoptosis in diabetes [ 2 , 11 , 12 ]. In this study, PRF treatment significantly improved endothelial cell viability from a high-glucose environment in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%